The Urgency of Legal Regulation for Do Not Resuscitate Orders in the Indonesian Healthcare System: A Comparative Study with the United Kingdom - Philip Anggra; Lewiandy (Dinasti Research, 2024)
The “Do Not Resuscitate” (DNR) order represents a critical ethical and legal directive within healthcare, providing patients the autonomy to decline cardiopulmonary resuscitation (CPR) at life’s end. This research examines the comparative legal frameworks and procedural implementations of DNR orders in Indonesia and the United Kingdom, highlighting the disparities and the impact on healthcare systems. Despite its recognition in Indonesia, DNR lacks specific legislation, influenced by cultural and religious perceptions that view end-of-life decisions as taboo. Conversely, the UK has established robust legal protocols under the NHS and the Mental Capacity Act 2005, ensuring DNR decisions align with patient rights and medical ethics. This study employs a qualitative comparative approach to analyze DNR policies, assessing the alignment of Indonesia’s practices with international standards and the UK’s structured approach. Through examining legal documents and health policies, this research proposes recommendations for Indonesia to enhance DNR regulatory frameworks, aiming to reconcile cultural sensitivities with the need for ethical clarity in medical decision-making. The findings suggest a pressing need for Indonesia to establish clear, culturally adapted DNR regulations to improve healthcare quality and respect for patient autonomy.